Weather Sensitivity of Downy Mildew and Alternaria Blight of Mustard in the Gangetic West Bengal, India (Journal of Science Foundation, 2013)
The infestation of disease-pest poses a considerable threat to rapeseed-mustard production in India. Alternaria blight [A. brassicicola (Schw.)] and downy mildew [Peronospora parasitica (Pers.) Kuntze] are the major diseases in lower Gangetic plains of India. As the rate of disease increase are dependent on weather factors, weather-based forewarning system may enable to guide farmers to take protection measures timely. The paper aims at to find the effect of weather on alternaria blight and downy mildew infestations. The weather data were compared with Percent Disease Index and the prevailing weather condition during peak disease intensity has been sorted out. It was observed that an increasing trend of last seven days average minimum temperature and relative humidity indicates more Alternaria blight and downy mildew infestation. DOI: http://dx.doi.org/10.3329/jsf.v8i1-2.14629 J. Sci. Foundation, 8(1&2): 77-81, June-December 2010